(untitled) (Research, Society and Development, 2020)
Objective: to carry out an evaluation of the hygienic-sanitary conditions of food sold in the Central Market in São Luís - MA. Methodology: For the hygienic-sanitary evaluation from the legal point of view of the Central Market, the checklist set out as Annex I in RDC No. 216 of September 15, 2004 from Anvisa / Ministry of Health, which deals with the Technical Regulation of Good Practices for Food Services. The form was filled out according to the apparent analysis of the place, judging the items arranged in it in positive or negative for different subjects such as structure and hygienic habits of the sellers. Results: In the Central Market, it was found that, regarding the physical structure of the site, of the 08 criteria analyzed, 05 were negative, showing the precariousness of the premises’ facilities. In the assessment of the hygiene and clothing habits of the handlers, of the 09 items analyzed, only 01 was attended to, while 08 were negative, although 02 of these were marked as positive. Regarding the aspects and quality of the food, of the 12 items analyzed, only 04 were in accordance with the standards, while 08 criteria obtained negative results. Conclusion: This study demonstrated the poor hygiene in the commercialization of food in the Central Market in São Luís - MA, from the premises of the place, quality and aspect of the food, to the hygienic habits and clothing of the handlers.